Pendidikan Humanis dan Implikasinya dalam Pembelajaran - Sidik, Firman (Yayasan Pusat Kemanusiaan dan Transformasi Sosial, 2023)
Humanist education is a learning model that in practice always fights for the rights of each individual to be able to actualize and explore their potential. In addition, humanist education is here to answer various educational problems that today seem to be a place of oppression of individual intellectuality and creativity because it places students as humans who do not have any knowledge and teachers become omniscient figures who are so dominant. With humanist education, learning is more conducive and provides recognition and trust in the uniqueness of each individual, besides that it can also create a more cooperative and democratic learning pattern. Thus, the practice of humanist education will have a positive impact on the development of the world of education and the statement that education is a place to humanize humans is not just a dream but it can really be realized in the reality of education.